HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP TENTANG KEJADIAN IKUTAN PASCA IMUNISASI DENGAN KEPATUHAN IBU DALAM MEMBERIKAN IMUNISASI DPT-HB-HIB DI WILAYAH KERJA PUSKESMAS LUBUK BUAYA KOTA PADANG - Lisa Rahmawati; Mahdalena Prihatin Ningsih (Jurnal Medikes (Media Informasi Kesehatan), 2020)
Based on the health profile of Indonesia in 2016, the number of cases of diphtheria in 2016 CFR (Case Fatality Rate) diphtheria, namely by 5.8%. Of all cases of diphtheria, amounting to 51% of them do not get vaccinated. Known from the annual report of Padang City Health Department 2017 Immunization coverage DPT-HB-Hib lows are in Lubuk Buaya Public Health Center (70.26%) of the 95% targets. The aim of research to determine the relationship level of knowledge and attitude about AEFI with Mother Compliance in giving immunization of DPT-HB-Hib in Lubuk Buaya Public Health Center. This research method is analytical survey with cross sectional study, data collection was done on January 22-March 12, 2019 in Lubuk Buaya Public Health Center. The population was mothers with babies aged 3-9 months, using a sampling technique purposive sampling with a sample of 66 respondents. Collecting data using questionnaires. Data were analyzed using a computerized with chi-square test. Results of univariate analysis obtained 60.6% of mothers do not obey the immunization of DPT-HB-Hib, 51.5% of mothers good knowledge, 56.1% of women have a negative attitude and 87.9% of infants with AEFI DPT-HB-Hib fever. The results of the bivariate analysis contained levels of knowledge about AEFI relationship with Compliance mother in immunization of DPT-HB-Hib (p = 0.002) and there is a relationship with Compliance AEFI Attitudes about Women in Giving Immunization DPT-HB-Hib (p = 0.039). It was concluded that there is a relationship between the level of knowledge and attitudes about AEFI maternal immunization compliance in providing the DPT-HB-Hib. For that is expected to increase outreach health workers about the DPT-HB-Hib and AEFI in order to minimize the perception and poor view of the DPT-HB-Hib and AEFI. Keywords : Immunization DPT-HB-Hib, Level of Knowledge, Attitude, AEFI